Compassion fatigue and transition shock of internship nursing students - Li, Zhi Ping; Kong, Ling Min; Wang, Xin; Qin, Jing Wen (Frontiers in Psychology, 2025)
BackgroundTransition shock experienced by nursing students during the middle and later stages of their clinical internships can significantly influence their post-graduation career decisions. Compassion fatigue, prevalent among interns, may exacerbate this transition shock. This study aims to investigate the current status of compassion fatigue and transition shock among nursing students in the middle and late phases of their internships and explore the correlation between these two phenomena.MethodsA cross-sectional study was conducted using convenience sampling to recruit 201 nursing interns from a tertiary a hospital between July 2022 and June 2023. Data were collected using the General Information Questionnaire, the Professional Quality of Life Scale (ProQOL-5), and the Transition Shock Scale for Undergraduate Nursing Students (UNSTS). Statistical analyses, including univariate analysis and multiple linear regression, were performed to examine the influencing factors of transition shock and the impact of compassion fatigue on transition shock.ResultsThe median scores for the three dimensions of compassion fatigue–compassion satisfaction, job burnout, and secondary trauma–were 26 (24, 30), 29 (26, 30), and 28 (25, 30), respectively. The median total score for transition shock was 48 (42, 54). Multiple linear regression analysis revealed that satisfaction with clinical teachers, compassion satisfaction, job burnout and secondary trauma were key influencing factors of transition shock, collectively accounting for 53.2% of its variance.ConclusionThe findings highlight the severity of compassion fatigue and transition shock among nursing students in the middle and later stages of their internships. Effective mitigation requires structured mentorship, psychological support systems, and resilience training, thereby supporting the retention and professional development of nursing students.